Indirect discrimination in the workplace : a comparison between South Africa and the United States of America - Moifo, Manjaku Jesaya (My University, 2012)
Indirect discrimination is a concept which originated from the United States of America. The concept came about after the failure of anti- discrimination legislation to improve the position of Black Americans, particularly in the employment field. The legislature realized that there are structural practices and policies, in the employment field which affect certain racial groups negatively. These practices of discrimination were not clearly defined hence the meaning and interpretation of the concept was left to the administrative body, the Equal Employment Opportunity Commission (EEOC) and the courts. The concept was imported into the South African jurisprudence after the inception of the government of National unity in 1994. The new government was committed to bring to an end all forms of discrimination which were in the past practiced against the Black community. Section 9(3) of the Constitution of South Africa Act 1996 (Act 108 of 1996) proscribed direct and indirect discrimination. These sections served as the basis for sections 6(1) of the Employment Equity Act 1998 (Act 55 of 1998) which proscribes “unfair direct and indirect discrimination” in any employment policy or practice. Its scope is wide and allows Plaintiffs to prove their claims in jurisdictions where it could have been very difficult for them to do so. While in the United States, statistical evidence is required to prove indirect discrimination, this is not the case in South Africa as seen in the landmark case of v Leonard Dingler Employee Representative Council v Leonard Dingler (PTY) LTD (1998) 19 ILJ 285 (LC). In this case when the Court gave its decision it simply relied on the facts of the case instead of complicated statistical evidence. Seemingly this will apply only in more obvious cases. In more complicated cases, Plaintiffs will still need to submit statistics to prove their claim.
Thesis (LLM. (Labour Law)) -- University of Limpopo, 2012
Keywords: Discrimination in employment; Job discrimination; Discrimination in employment -- Law and legislation; Equal opportunity in employment; Unfair labor practices -- South Africa; Employment discrimination